Church re-creation reintroducing social interaction in Christ Commission Fellowship (CCF) Imus Church Community for improved personal fulfillment of church youths - Evardone, Alyssa Mae C.; Gozon, Patrick Andrew E. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
While the implementation of social distancing paved the way for slowing down the spread of the virus and preventing the Philippine’s health care systems from being overwhelmed during the COVID-19 pandemic, social isolation has been suppressing human’s hard-wired impulses for connection, especially among the church youth. The importance of churches and other places of worship in the post-pandemic recovery has been highlighted with its provision of infrastructure for care, support, and socialization for people’s holistic well-being. However, a worldwide decline among church youth gatherings has been observed with one factor being the limited spaces for non-regulated social interaction, specifically in Christ Commission Fellowship (CCF) Imus. Worship is known to require “whole people'' situated in time and place in fellowship with others, thus in-person interaction in churches would still be necessary despite the availability of online services. The impact of overlooking the spiritual dimension of human well-being can be seen with the increasing concerns regarding mental health and an evident lack of positive outlook against adversity of young people today. Modern Christian church buildings have been stepping out from being solely used for sacred activities by integrating recreational and educational facilities to reach out to the youth more effectively. This thesis explores the gap of such existing developments in the context of the new normal and seeks timely and more relevant approaches on the types of social interaction that could be adapted to reestablish the essence of in-person interrelation for spiritual engagement among the church youth by designing flexible and adaptive church buildings.
include appendices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Church buildings -- Imus (Cavite); Church buildings -- Recreational use -- Imus (Cavite); Church youth